Pembuatan Hand Sanitizer Otomatis bagi Jama’ah Masjid “Attawwaabiin” Kelurahan Pisang Candi Kota Malang - Stanislaus Yoseph; Sari Yuniarti; Sunarjo Sunarjo; Subairi Subairi; Laksni Sedyowati; Sufiyanto Sufiyanto (Universitas Pendidikan Indonesia Kampus Purwakarta, 2022)
The covid-19 pandemic initiates the emergence of the social distancing concept and the implementation of health protocols. This also happens in worship places, which are public places and are at risk of spreading the Covid-19 virus. For such reason, strict health protocols need to be carried out when washing hands with hand sanitizer. The use of hand sanitizers is believed to be able to kill viruses well, but manual spraying can increase the spread of the virus. This program aims to make automatic hand sanitizer spraying devices placed in front of the Attawwaabiin Mosque entrance, Pisang Candi Village, Malang City. The implementation method consisted of program observation and the manufacture of an automatic hand sanitizer spraying device, including the preparation of tools and components, the assembly stage, the trial and repair stage, and the stage of providing tools to partners. The result of this program is a tool that is specially assembled so that the spraying of hand sanitizer can be done automatically without touching other media so that it can help reduce the spread of the virus so that the congregation of the mosque can carry out their worship with a sense of security and comfort.